Analisis Kerangka Kerja Asset dan Leability Management (ALMA) - Febria Lesmita Sari; Nurul Huda; Nurnasrina N; Nola Fibriyani Bte Salman (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Asset and Liability Management (ALMA) in Islamic banking, the management of bank assets and liabilities to achieve a balance between profitability and risk. Using literature studies, this study identifies key elements of ALMA, such as policy setting, data collection, scenario analysis, liquidity management, gap management, and foreign exchange management. The ALMA framework is designed to maximize revenue and control risks such as financing risk, liquidity risk, pricing risk, and foreign exchange risk. ALMA allows banks to maintain balance sheet stability and face market changes more adaptively, supporting optimal financial performance.